Sistem Informasi Pengajuan Klaim Berbasis Website di PT. Asuransi Kredit Indonesia Kantor Cabang Bogor - Pranabella Syafitri, Putriyana; Kamilah, Nurul; Fatimah, Fety (Rifa'Institute, 2023)
Credit Insurance is insurance protection to the insured (banks) against risks or credit that is not paid by the debtor which causes a claim to the insurer (insurance). A claim is a claim for payment of compensation due to the debtor not fulfilling its obligations. The purpose of this research is because verification of claim completeness data is still done manually, so that information related to completeness status is delayed, this is due to the absence of a system that provides information effectively and efficiently in the claims section. Based on this, a web-based claim submission information system was designed using the PHP programming language and MySQL database. The research method used in making this information system is by observation, questionnaires, and literature studies as well as the development method using the waterfall method. The result of this research is an application of information for submitting claims which is expected to make it easier for companies to minimize the data verification process more effectively.